THE READINESS OF YOGYAKARTA CITY GOVERNMENTâS EMPLOYMENT SECTOR TOWARDS THE ASEAN ECONOMIY COMMUNITY (AEC) COMPETITION IN 2016 - Husni, Al; Nurmandi, Achmad (Universitas Muhammadiyah Yogyakarta, 2018)
The ASEAN Globalization Level issues a strict commitment between ASEAN countries, regarding the agreement of the ASEAN Economic Community (AEC). The agreement that leads to competition in the various sectors, one of which focuses on the labor sector, is a major requirement in service factors. The concept of Mutual Recognition Arrangement (MRA) is an applicable norm in the recognition of skilled and certified labors. Judging at the competitiveness of the employment data availability and the growing number of Indonesian labors, then implications are made for the regions. The present research is aimed at the readiness of the Yogyakarta City Governmentâs employment sector in the face of the ASEAN Economic Community (AEC) competition in 2016